Biophysical Stimulation in Athletes’ Joint Degeneration: A Narrative Review - Lorenzo Moretti (MDPI AG, 2021)
Osteoarthritis (OA) is the most prevalent degenerative joint disease and the main cause of pain and disability in elderly people. OA currently represents a significant social health problem, since it affects 250 million individuals worldwide, mainly adults aged over 65. Although OA is a multifactorial disease, depending on both genetic and environmental factors, it is reported that joint degeneration has a higher prevalence in former athletes. Repetitive impact and loading, joint overuse and recurrent injuries followed by a rapid return to the sport might explain athletes’ predisposition to joint articular degeneration. In recent years, however, big efforts have been made to improve the prevention and management of sports injuries and to speed up the athletes’ return-to-sport. Biophysics is the study of biological processes and systems using physics-based methods or based on physical principles. Clinical biophysics has recently evolved as a medical branch that investigates the relationship between the human body and non-ionizing physical energy. A physical stimulus triggers a biological response by regulating specific intracellular pathways, thus acting as a drug. Preclinical and clinical trials have shown positive effects of biophysical stimulation on articular cartilage, subchondral bone and synovia. This review aims to assess the role of pulsed electromagnetic fields (PEMFs) and extracorporeal shockwave therapy (ESWT) in the prevention and treatment of joint degeneration in athletes.